We have E(x) = (x^3-3x-2)/(x^3+1+3x^2+3x). We have to solve E(x) = sqrt 3 - sqrt 2.

E(x) = sqrt 3 - sqrt 2

=> E(x) = (x^3-3x-2)/(x^3+1+3x^2+3x) = sqrt 3 - sqrt 2

=> (x^3-3x-2)/(x + 1)^3 = sqrt 3 - sqrt 2

=> (x^3 - x - 2x - 2)/(x + 1)^3 = sqrt 3 - sqrt 2

=> (x(x^2 - 1) - 2(x + 1)/(x + 1)^3 = sqrt 3 - sqrt 2

=> (x(x - 1)(x + 1) - 2(x + 1))/(x + 1)^3 = sqrt 3 - sqrt 2

=> (x + 1)( x^2 - x - 2)/(x + 1)^3 = sqrt 3 - sqrt 2

=> (x^2 - x - 2)/(x + 1)^2 = sqrt 3 - sqrt 2

=> (x^2 - 2x + x - 2)/(x + 1)^2 = sqrt 3 - sqrt 2

=> (x(x -2) +1(x - 2)/(x + 1)^2 = sqrt 3 - sqrt 2

=> (x+1)(x -2)/(x + 1)^2 = sqrt 3 - sqrt 2

=> (x -2)/(x + 1) = sqrt 3 - sqrt 2

=> x - 2 = (sqrt 3 - sqrt 2)(x + 1)

=> x - 2 = (x* sqrt 3 - x* sqrt 2 + sqrt 3 - sqrt 2)

=> x - x*sqrt 3 + x*sqtr 2 = 2 + sqrt 3 - sqrt 2

=> x( 1- sqrt 3 + sqrt 2) = 2 + sqrt 3 - sqrt 2

=> x = (2 + sqrt 3 - sqrt 2) / ( 1- sqrt 3 + sqrt 2)

**The required value of x = (2 + sqrt 3 - sqrt 2) / ( 1- sqrt 3 + sqrt
2)**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.